Effect of Green Tea Extract-Enriched Diets on Insulin and Leptin Levels, Oxidative Stress Parameters and Antioxidant Enzymes Activities in Obese Mice - Bártíková Hana; Boušová Iva; Matoušková Petra; Szotáková Barbora; Skálová Lenka (Polish Journal of Food and Nutrition Sciences)
Green tea and green tea extracts (GTE) are often incorporated into diet intended to weight reduction, although the information about their efficacy in obese individuals is insufficient. The present study was designed to follow up the effect of defined and standardized GTE in mice with obesity induced by monosodium L-glutamate. Obese mice were fed with GTE-supplemented diet in three dosage regimens: 28-day and 3-day intake of 1 g GTE in 1 kg of diet and 28-day intake of 0.1 g GTE in 1 kg of diet. The information on body weight, food intake, oxidation stress parameters in blood and antioxidant enzymes activity in liver and small intestine was obtained. High doses of GTE decreased the specific activities of glutathione reductase and catalase and increased concentrations of malondialdehyde in blood. Specific activities of antioxidant enzymes in the liver and small intestine were not altered after GTE treatment except the decrease of NAD(P)H:quinone oxidoreductase activity. Our results showed that GTE did not affect average body weight and did not markedly improve antioxidant status in glutamate-induced obese mice. Moreover, intake of high doses of GTE made antioxidant defense in obese animals even worse.